2014
DOI: 10.1016/j.yqres.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Last glacial maximum environments in northwestern Patagonia revealed by fossil small mammals

Abstract: Comparisons of historical and modern assemblages of mammals can yield important insights into patterns and processes of environmental change. Here, we present the first analyses of small mammal assemblages present in northern Patagonia during the last glacial maximum (LGM). Using remains obtained from owl pellets excavated from an archeological cave site (Arroyo Corral I, levels VII–V, carbon dates of 22,400–21,530 cal yr BP), we generate estimates of the minimum number of individuals for all species detected;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
17
0
2
Order By: Relevance
“…Prevosti et al . () showed that between the Late Pleistocene and late Holocene, D. avus occupied a large area (estimated at 762 351 km²) that encompassed the Pampean region and Patagonia (including Tierra del Fuego) that experienced significant climatic and environmental changes, particularly in the Holocene (Clapperton, ; Markgraft, ; Prieto & Stutz, ; Tonni, Cione & Figini, , ; Mancini, ; Schäbitz, ; Grill et al ., ; Mancini et al ., ; Borromei et al ., ; Pardiñas & Teta, ; Tammone et al ., ). Climatic variations recorded in the last 1000 cal years, including the Medieval Warm Period and the Little Ice Age ‘events’ impacted the southern cone of South America (Politis, ; Tonni et al ., , ; Deschamps, Otero & Tonni, ; Favier‐Dubois, ; Borromei & Quattrocchio, ; Waldmann, ; Tonello & Prieto, ; Ponce et al ., ; Pardiñas, Udrizar Sauthier & Teta, ; Del Puerto et al ., ; Mancini & Graham, ; Teta et al ., ), but there is no evidence to suggest that these climatic anomalies were more deleterious than those which characterized the Late Pleistocene–Holocene, the middle Holocene, or even the Neoglacial advance (Mancini et al ., ; Tonello & Prieto, ; Mancini & Graham, ).…”
Section: Discussionmentioning
confidence: 97%
“…Prevosti et al . () showed that between the Late Pleistocene and late Holocene, D. avus occupied a large area (estimated at 762 351 km²) that encompassed the Pampean region and Patagonia (including Tierra del Fuego) that experienced significant climatic and environmental changes, particularly in the Holocene (Clapperton, ; Markgraft, ; Prieto & Stutz, ; Tonni, Cione & Figini, , ; Mancini, ; Schäbitz, ; Grill et al ., ; Mancini et al ., ; Borromei et al ., ; Pardiñas & Teta, ; Tammone et al ., ). Climatic variations recorded in the last 1000 cal years, including the Medieval Warm Period and the Little Ice Age ‘events’ impacted the southern cone of South America (Politis, ; Tonni et al ., , ; Deschamps, Otero & Tonni, ; Favier‐Dubois, ; Borromei & Quattrocchio, ; Waldmann, ; Tonello & Prieto, ; Ponce et al ., ; Pardiñas, Udrizar Sauthier & Teta, ; Del Puerto et al ., ; Mancini & Graham, ; Teta et al ., ), but there is no evidence to suggest that these climatic anomalies were more deleterious than those which characterized the Late Pleistocene–Holocene, the middle Holocene, or even the Neoglacial advance (Mancini et al ., ; Tonello & Prieto, ; Mancini & Graham, ).…”
Section: Discussionmentioning
confidence: 97%
“…Fossil remains of living species are known from Patagonia, central and southern Chile and north‐western Argentina and are restricted to the Late Pleistocene–Holocene (e.g. Pardiñas et al., ; Ortiz et al., ; Tammone et al., ).…”
Section: Main Taxonomic Hypotheses For the Genera Now Referred To Abrmentioning
confidence: 99%
“…Although multiple studies have used modern mammal communities as a baseline for identifying differences in fossil faunas and inferring associated alterations to environmental conditions (e.g. Hadly, 1999; Montuire, 1999; Pardiñas and Teta, 2013; Tammone et al, 2014; Terry, 2010; Vigne and Valladas, 1996), our analyses raise concerns regarding the suitability of modern data for this purpose, particularly in regions that have experienced substantial recent modification due to human agricultural and land use practices. Minimally, reconstructions of fossil faunas and environments should consider the extent to which comparative data from modern assemblages and habitats reflect recent (i.e.…”
Section: Introductionmentioning
confidence: 99%